Improving Patient Care: Expansion of Access to Free Clinics - Anahis Davidian; Gail Bloom (Patient Experience Journal)
Free clinics provide free or reduced-fee healthcare services for uninsured, underserved, and marginalized populations. Free clinics may be the only source of primary care for socioeconomically disadvantaged individuals lacking health insurance. However, consistently understaffed and underfunded free clinics are struggling to meet growing needs. The demand for services results in long waitlists with long wait times. Most free clinics rely on volunteer providers and staff due to limited financial resources. This case study proposes recommendations that can address the challenges of funding limitations while improving free clinics' ability to offer more accessible and equitable care to serve a greater proportion of people seeking health care. Suggested solutions include improving clinical workflow efficiency, coordinating patient referral networks, and allocating greater safety net funding from federal and local governments. In addition, incentivizing healthcare profession students to engage with free clinics within their communities would increase the number of available providers for assisting with the work of free clinics.